Role of vascularised fibula graft in the surgical management of radiation-induced midshaft femoral fractures. Case report and literature review - Monique Khasin; Genevieve M. Darcy; Eldon Mah; Claudia Di Bella (World Journal of Surgical Oncology)
Abstract Background Post-radiation fractures (PRF) are a recognised complication of radiation treatment for soft tissue sarcomas. They have a low incidence and typically occur up to 5 years following treatment, more commonly affecting the pelvis, ribs and femur. Due to radiation-induced changes in bone, PRFs typically require more complicated intervention compared to post-trauma fractures, however, limited literature exists, particularly in regards to mid-shaft femoral PRFs. We report a case of a mid-shaft femoral PRF managed with a modified onlay free vascularised fibular grafting (FVFG). Case presentation A 40-year-old male with a history of left quadriceps clear cell sarcoma successfully treated with wide local excision, chemotherapy and radiotherapy 18 years prior presented with a displaced oblique pathological fracture of his left femoral shaft. He was initially treated operatively with intramedullary nailing, however, repeat imaging at the one-year post-operative review demonstrated persistent hypotrophic non-union of the fracture. 16 months following the initial fracture, the patient underwent further surgical intervention with implantation of a modified onlay FVFG to the anterior aspect of the distal femur without nail removal. One-year post-revision, the patient was pain-free with normal mobility and imaging of both the graft and fracture site demonstrated complete union. Conclusion Despite their operative complexity, we suggest that FVFGs should be considered for treating non-union of mid-shaft femoral PRFs due to their ability to promote healing and bone union in irradiated bone. Here we describe an original technique of a modified onlay FVFG which can be used in PRFs, and we have put this technique in the context of the current literature in FVFG.